1982
DOI: 10.1135/cccc19822912
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids of Rauvolfia salicifolia GRISEB species

Abstract: Dedicated to Professor Holger Erdtman on the occasion 0/ his 80th birthday.From the endemic Cuban species Rauuol/ia salicl/olia GRISEB nine alkaloids were isolated of which the following seven had been already described: ( + )-ajmalidine (I), ( -)-reserpiline (11), ( -)-iso-The structure of ( -)-raucubaine (VI11) had been previously determined by X-ray diffraction and the structure of the alkaloid (-)-raucubainine (IX) was suggested on the basis of its conversion to ( -)-raucubaine (V Ill). The absol ute confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…The mass spectrum of vallesamidine differed from that Part XCVII in the series Plant Substances; Part XCVI: see ref. (1). This work represents a part of the Thesis of A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass spectrum of vallesamidine differed from that Part XCVII in the series Plant Substances; Part XCVI: see ref. (1). This work represents a part of the Thesis of A.…”
Section: Resultsmentioning
confidence: 99%
“…Quel. (Tricholomataceae) are used for the treatment of dizziness, headache, neurasthenia, insomnia, numbness in limbs and infantile convulsion (1). For investigation of the effective principles of this drug we have studied its chemical constituents, Recently, Midland (2) and Donnelly (3) reported that two new sesquiterpenoid aromatic esters, which have antibacterial activity, were isolated from A. mellea.…”
Section: Introductionmentioning
confidence: 99%
“…has revealed the presence of (+)-ajmalidine in the root bark and (+)-vellosimine in the stem bark. 57 The presence of (-)raucubaine (136) in the leaves was confirmed, together with a closely related alkaloid, (-)-raucubainine (1 39), which is converted into raucubaine on reaction with methanol in acid solution. Raucubainine thus has the same gross structure as quaternoxine, but the two bases appear not to be identical, and hence may differ in the configuration of the epoxide function.…”
Section: Sarpagine-ajmalinepicraline Groupmentioning
confidence: 92%
“…Ajmalicine, reserpiline, and yohimbine were isolated from the tree bark, and ajmalicine and reserpiline from the leaves. 57 Hunteria congofana Pichon contains 23 alkaloids, including pleiocarpamine and its 2,7-dihydro-derivative from this group. 58 The nineteen alkaloids extracted from the stem and root bark of New Caledonian Afstonia pfumosa Labill.…”
Section: Corynantheine-heteroyohimbine-yohimbine Group and Related Ox...mentioning
confidence: 99%
“…Also, in Brazilian folk medicine it was described to have curare-like properties [ 87 ]. Moreover, (+)-vellosimine was extracted from different species of Rauwolfia that are widely dispersed thought Asia and Africa [ 88 , 89 , 90 , 91 ]. These plants are broadly used in traditional Chinese medicine for the treatment of hypertension [ 89 , 92 ] neuralgia, and migraine [ 93 ].…”
Section: Pictet–spengler Reaction In the Total Synthesis Of Naturamentioning
confidence: 99%